Impact of Baseline Characteristics on the Effectiveness of Disorder-Specific Cognitive Behavioral Analysis System of Psychotherapy (CBASP) and Supportive Psychotherapy in Outpatient Treatment for Persistent Depressive Disorder - Serbanescu, Ilinca; Backenstrass, Matthias; Drost, Sarah; Weber, Bernd; Walter, Henrik; Klein, Jan Philipp; Zobel, Ingo; Hautzinger, Martin; Meister, Ramona; Härter, Martin; Schramm, Elisabeth; Schoepf, Dieter (Frontiers in Psychiatry, 2020)
Importance: In the treatment of persistent depressive disorder (PDD), disorder-specific Cognitive Behavioral Analysis System of Psychotherapy (CBASP) has been shown to be superior to Supportive Psychotherapy (SP) in outpatients.. It remains to clear which subgroups of patients benefit equally and differentially from both psychotherapies. Objective: To identify those patient-level baseline characteristics that predict a comparable treatment effectiveness of CBASP and SP and those that moderate the differential effectiveness of CBASP compared to SP. Design, setting and participants: In this analysis of a 48-week multicenter randomized clinical trial comparing CBASP to SP in adult antidepressant-free outpatients with early-onset PDD, we evaluated baseline variables from the following domains as potential predictors and moderators of treatment effectiveness: socio-demography, clinical status, psychosocial and global functioning, life quality, interpersonal problems, childhood trauma, treatment history, preference for psychotherapy, and treatment expectancy. Interventions: A 48-week treatment program with 32 sessions of either CBASP or SP. Main outcomes and measures: Depression severity measured by the 24-item Hamilton Rating Scale for Depression (HRSD-24) at week 48. Results: From N=268 randomized outpatients, N=209 completed the 48-week treatment program. CBASP completers had significantly lower post-treatment HRSD-24 scores than SP completers (meanCBASP=13.96, sdCBASP=9.56; meanSP=16.69, sdSP=9.87; p=0.04). A poor response to both therapies was predicted by higher baseline levels of clinician-rated depression, elevated suicidality, comorbid anxiety, lower social functioning, higher social inhibition, moderate-to-severe early emotional or sexual abuse, no preference for psychotherapy, and the history of at least one previous inpatient treatment. Moderator analyses revealed that patients with higher baseline levels of self-rated depression, comorbidity of at least one Axis-I disorder, self-reported moderate-to-severe early emotional or physical neglect, or at least one previous antidepressant treatment, had a significantly lower post-treatment depression severity with CBASP compared to SP (all p<.05). Conclusions and relevance: A complex multifactorial interaction between severe symptoms of depression, suicidality, and traumatic childhood experiences characterized by abuse, social inhibition and anxiety may represent the basis of non-response to psychotherapy in patients with early onset PDD. Specific psychotherapy with CBASP might, however, be more effective and recommendable for a variety of particularly burdened patients compared to SP.